Austrian-Hungarian Diplomatic Relations: 2017-2021 - Eniko Gyorkos (European Scientific Journal, ESJ, 2022)
Since Sebastian Kurz was elected Chancellor in 2017, Austrian internal politics has changed significantly, and there is a visible rapprochement with several countries in the region, including Hungary. There is a consensus between Hungary and Austria on many issues, including the defense of Christian culture, the European way of life, and the protection of society. Both countries are urging the establishment of a common European military force and the strengthening of border guards. Austria is Hungary's second most important trading partner in terms of total trade volume, and Austria is one of the largest investors in Hungary today. Considering these points, it is worth examining how the system of diplomatic relations between the two countries has developed in recent years.